Encountering the Shadow: Working with Negativity in the Therapeutic Process - Heinrich-Clauer, Vita (Bioenergetic Analysis, 2020)
The interacting unconscious in the contact between therapist and client, the (self) sabotage and destructiveness observed as resistance in the contact to oneself and to others, is explained conceptually and illustrated with case studies. Therapeutic techniques will be presented which allow a creative and energizing, vocally expressive handling of the hostility bound up in the introject, in which the patient «embraces” their own shadow. The bases for the practical work are the well-known concepts and interventions of Bioenergetic Analysis, and this perspective is extended by reference to the anatomical-functional and the neurovegetative contexts of vocal expression. The tongue is of particular importance as it is a universal organ of expression for rejection, contempt, aversion as well as for desire. The familiar and the new are placed within a specific therapeutic framework.